Serum cortisol concentration in horses with heaves treated with fluticasone proprionate over a 1 year period. (February 2015) - Munoz, Trohadio; Leclere, Mathilde; Jean, Daniel; Lavoie, Jean-Pierre
Highlights: We administered inhaled fluticasone proprionate for a year to heaves-affected horses. We measured serum cortisol in horses treated with fluticasone and antigen avoidance. Inhaled fluticasone at therapeutic dosages can suppress cortisol for 8–24 h. Abstract: The purpose of this study is to measure the effect of long-term administration of inhaled fluticasone proprionate on cortisol concentrations in heaves-affected horses. Eleven horses with heaves were treated with fluticasone at least once daily at dosages required to improve lung function or with antigen avoidance alone for 1 year. Morning serum cortisol was measured before and after 10, 30, 110, 190, 230, 280, and 320 days of treatment. Cortisol was also measured in the afternoon of day 330. Cortisol was significantly lower in the Fluticasone group on days 30, 110, and 190 when compared with the Antigen avoidance group. Cortisol measured on day 330 was also significantly lower in the Fluticasone group. Results indicate that inhaled fluticasone, when administered at therapeutic dosages, can significantly suppress serum cortisol concentrations for 8–24 h. The clinical significance of this finding remains to be ascertained, as no clinical signs were associated with this cortisol suppression.